2006
DOI: 10.1016/j.trstmh.2005.06.033
|View full text |Cite
|
Sign up to set email alerts
|

Identifying risk factors for tungiasis and heavy infestation in a resource-poor community in northeast Brazil

Abstract: Tungiasis is a neglected parasitic skin disease caused by penetration of female sand fleas into the epidermis. The ectoparasitosis is widespread in resource-poor communities in South America, the Caribbean and sub-Saharan Africa. To identify risk factors for the presence of sand fleas and severe infestation in an endemic community, we examined the entire population of a traditional fishing village for the presence of embedded sand fleas and determined the number and type of lesions. Demographic, behavioural an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
119
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(128 citation statements)
references
References 13 publications
6
119
0
3
Order By: Relevance
“…The report indicates that, similar to recent accounts from other African countries such as Nigeria [2,16], Madagascar [17] and Cameroon [18,19], the disease may also reach high parasite loads in individuals in Tanzania, with consequently severe pathology, in contrast to milder cases reported by returning tourists. The patient was living under conditions previously described as risk factors in studies from Brazil and Nigeria [20,21]: i.e., people living under poor conditions, usually in houses with floors made of sand or mud. The type of soil in the area is red clay soil which gives much dust during the dry season.…”
Section: Discussionmentioning
confidence: 99%
“…The report indicates that, similar to recent accounts from other African countries such as Nigeria [2,16], Madagascar [17] and Cameroon [18,19], the disease may also reach high parasite loads in individuals in Tanzania, with consequently severe pathology, in contrast to milder cases reported by returning tourists. The patient was living under conditions previously described as risk factors in studies from Brazil and Nigeria [20,21]: i.e., people living under poor conditions, usually in houses with floors made of sand or mud. The type of soil in the area is red clay soil which gives much dust during the dry season.…”
Section: Discussionmentioning
confidence: 99%
“…People occasionally visiting other areas were excluded. The selected individual's clinical evaluation was conducted to reveal the severity of the infection [10].…”
Section: Resultsmentioning
confidence: 99%
“…Tunga penetrans complete its life cycle in the sandy or muddy floor of the houses and it premises. So poor houses with muddy or sandy soil, unhygienic health behavior of the population, all these factors affects the rate of infection [10][11][12]. Previous studies revealed that there were high prevalence of disease in sheep, dog and pig [8,13,14].…”
mentioning
confidence: 99%
“…Vários estudos também corroboram que crianças são mais susceptíveis à tungíase, devido, principalmente, a seu comportamento em áreas pobres onde ocorre a doença, como andar descalço ou brincar em contato direto com o solo. 9,12,25,26 Alguns autores também acreditam que a prevalência da tungíase tem relação com a idade: a queratinização da pele dos pés dos adultos dificultaria a penetração da pulga. 27,28 Em relação ao sexo, os estudos disponíveis são discordantes.…”
Section: Discussionunclassified
“…Em áreas endêmicas, as altas infestações estão associadas, principalmente, a condições precárias de moradia, falta de educação em saúde e presença de animais. 25 As infecções secundárias são muito comuns na tungíase, causadas por uma grande variedade de microorganismos patogênicos. 13,31,33,34 Entre as formas de prevenção, as mais conhecidas dos profissionais foram o uso de calçados e as práticas de higiene.…”
Section: Discussionunclassified